Ecological testing results of the winter bread wheat varieties and lines developed in the FSBSI «ARC «Donskoy» in the Kursk region - A. Ya. Aidiev; D. M. Marchenko; М. М. Ivanisov; А. А. Emeliyanova; E. V. Logvinova (Зерновое хозяйство России, 2022)
The current paper has presented the ecological testing results of the winter bread wheat varieties and lines developed in the FSBSI «ARC «Donskoy» in the soil and climatic conditions of the Kursk region. The purpose of the current study was to identify promising varieties and breeding lines of winter bread wheat adapted to the conditions of the Central Blackearth region of the Russian Federation. The objects of the study at the initial stage (2018–2020) were such winter wheat varieties included in the State List of Breeding Achievements as ‘Volny Don’, ‘Krasa Dona’, ‘Donskaya Step’, ‘Volnitsa’, ‘Etyud’, ‘Zhavoronok’, ‘Yermak’, and in the following years (2020–2021) there were studied from 15 to 40 lines developed on the basis of hybridization in the «ARC «Donskoy». As a result of ecological testing, there has been identified a number of varieties and lines that are most adapted to the soil and climatic conditions of the Kursk region. A new joint variety of winter bread wheat ‘Vertikal’ has been sent to the State Variety Testing. Productivity of the variety ‘Vertikal’ in the Kursk FANC varied from 50.1 to 71.9 hwt/ha; in SamRC RAS it was from 32.4 to 71.6 hwt/ha; in the Research Institute of Agriculture of the Crimea it was from 38.7 to 49.5 hwt/ha. Productivity of the standard varieties ‘Moskovskaya 39’, ‘Skipetr’ and ‘Ermak’ was 47.8–52.0 hwt/ha, 25.3–63.9 hwt/ha, 37.0–42.2 hwt/ha, respectively. Ecological testing was carried out in the breeding crop rotation of the Kursk Federal Agricultural Research Center (FSBSI Kursk FANC). The soil cover of the experimental plot was represented by typical heavy loamy blackearth (chernozem). The forecrop was black fallow. Sowing was carried out in an ordinary way with a row spacing of 15 cm, with a seeder SKS-6-10. The plots were with an accounting area of 10 m2 in six repetitions, the seeding rate was 500 germinating grains per 1 m2, the standard variety ‘Moskovskaya 39’ was sown every 10 numbers. Lodging and winter hardiness and structural analysis of plants was estimated according to the methods of the State Variety Testing of Agricultural Crops. Over the years of study, there have been identified the winter bread wheat lines with economically valuable traits that exceeded the standard one and could be used in further breeding work. Breeding varieties on a cooperative basis makes it possible to expand the area of distribution of research by breeding centers to develop new varieties in other ecological and geographical conditions.